Upaya Meningkatkan Keterampilan Menulis Bahasa Inggris Melalui Teknik EGRU Pada Siswa Kelas X SMK Negeri 1 Ende - Separ, Fransiskus Maria (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to improve students' writing skills and improve mastery of sentence patterns and vocabulary in learning English and improve students' writing learning outcomes, especially in class X of SMK Negeri 1 Ende, Mautapaga Village, East Ende District, Ende Regency, East Nusa Tenggara. The subjects of this research were 39 students of class X- SMK Negeri 1 Ende. This research was carried out in three cycles, namely cycle I presented short message texts with the topic